Optimizing chicken litter biochar and Eygpt Rock Phosphate to improve dry matter production of maize reducing phosphorus fixation in a tropical acid soil - Medin, Simon (2019)
Soluble inorganic Phosphorus (P) in soils readily reacts with Aluminium and Iron because P predominate in soil solution, depending on soil pH, and remains immobile due to its fixation with hydrous and oxides. Biochar which bear functional groups with negative charges, have reported to improve acid soils with biochar or a mixture of biochar increased total P, available P, inorganic P fractions, to improve soil porosity and surface area. However, there is lack of information on the optimum use of biochar and P fertilizers to reduce P fixation especially for Egypt Rock Phosphate (ERP). The objectives of this study were to: (i) determine the optimum amount of P and biochar that could reduce phosphorus fixation and (ii) improve dry matter production of Zea mays L. by reduction of phosphorus fixation using biochar. Different rates of chicken litter biochar (75%, 50%, and 25%) and ERP (75%, 50%, and 25%) were evaluated in incubation study (for 30, 60, and 90 days) and pot studies. Soil samples were analysed on selected soil physico-chemical properties, nutrient uptake, and growth variable properties before and after leaching, incubation, and pot studies using standard procedures. Incubation study results showed that total P, pH, K, and Mg of leachates with 75% biochar were significantly higher due to the liming effect of the chicken litter biochar. The pH, total C and P, exchangeable P, water soluble P, after 30 days of leaching were significantly higher than that of the existing fertilization recommendation. The use of 75% biochar of 10 t ha-1 with 50% and 25% ERP showed significant retention and nutrients availability because of reduction of Al and Fe hydrolysis. Soil pH, total P, available P, and water soluble P increased in the treatments with 75% biochar for incubation study. Total acidity, exchangeable Al3+, and H+ were significantly reduced by the chicken litter biochar. The use of 75% of 10 t ha-1 biochar with 25% ERP of the existing recommendation enhance phosphate release from ERP amended by minimizing soil Al and Fe hydrolysis. The results in the pot study suggest the use of 75% biochar of 10 t ha-1 with 25% ERP increased soil P availability, P uptake and dry matter yield of Zea mays L. Maize productivity can be improved by using chicken litter biochar with 25% reduction of ERP. Generally, improving phosphorus use efficiency and yield of Zea mays L. cultivation on an acid soil using chicken litter biochar reduced chicken litter biochar and P fertilizer application rate, improved P availability, P uptake, and increase yield of Zea mays L. This study may only be applicable to tropical acid soils and it will as well contribute to the optimum utilization of P fertilizers and chicken litter biochar on tropical acid soil to improve Zea mays L. production. Further studies especially field trials are essential for consolidation of the research findings which reported in the thesis.